Pengaruh Kepercayaan, Kemudahan dan Promosi terhadap Keputusan Pembelian Secara Online di TikTok Shop: (Studi pada Pengguna TikTok Shop Daerah Istimewa Yogyakarta) - Siti Khotijah; Krisna Mutiara Wati (Jurnal Kajian dan Penalaran Ilmu Manajemen, 2024)
TikTok Shop is an innovative social commerce platform that connects shoppers and merchants to create a unique, simple, and enjoyable purchasing experience. The purpose of this study is to ascertain how TikTok Shop users in the Special Region of Yogyakarta make online purchase decisions and how much value they place on convenience, trust and promotion. With a total of 100 respondents, the research method uses a quantitative approach to gather questionnaire data via a Google Form. Strategies that TikTok Shop users in the Special Region of Yogyakarta make partial and simultaneous decisions about online purchases based on factors such as convenience, trust, and promotion.